2015
DOI: 10.1016/j.algal.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Baltic Sea microalgae transform cement flue gas into valuable biomass

Abstract: We show high feasibility of using cement industrial flue gas as CO 2 source for microalgal cultivation. The toxicity of cement flue gas (12-15% CO 2 ) on algal biomass production and composition (lipids, proteins, carbohydrates) was tested using monocultures (Tetraselmis sp., green algae, Skeletonema marinoi, diatom) and natural brackish communities. The performance of a natural microalgal community dominated by spring diatoms was compared to a highly productive diatom monoculture S. marinoi fed with flue gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…Euglenoids are common in nutrient rich and eutrophied waters and were highly competitive in the CO 2 treatment but considerably less so in the FG treatment where Euglenoids were replaced by green algae. Flue gas did affect negatively the biovolume of Euglenoids compared to CO 2 , although cement FG has been shown to be a suitable source of CO 2 for Baltic microalgae . The presence of an inhibitory compound in the cement FG that targets specifically Euglenoids cannot be dismissed.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Euglenoids are common in nutrient rich and eutrophied waters and were highly competitive in the CO 2 treatment but considerably less so in the FG treatment where Euglenoids were replaced by green algae. Flue gas did affect negatively the biovolume of Euglenoids compared to CO 2 , although cement FG has been shown to be a suitable source of CO 2 for Baltic microalgae . The presence of an inhibitory compound in the cement FG that targets specifically Euglenoids cannot be dismissed.…”
Section: Discussionmentioning
confidence: 94%
“…Environmental fluctuations, contamination by pathogens and grazers often undermine industrial‐scale algae cultivation. Ongoing research, using fundamental ecological principles, particularly the stability and resilience of diverse microalgal communities, as a powerful approach toward the sustainability of industrial‐scale algal cultivation has received increasing attention . Moreover, industrial flue gas can be an inexpensive source of CO 2 used in the cultivation process .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be highlighted that logistics, preparation, and use according to the regional particularities can be a differentiator (e.g., seawater, brackish, freshwater and wastewater, cheap nutrients and fertilizers, flue gas from local sources: power-plant, cement industry, ethanol mills, biogas upgrading etc.) [20,36,38,[92][93][94][95][96][97][98][99].…”
Section: The Basis Of the Integral Biorefinery Conceptmentioning
confidence: 99%
“…Among these published papers, most of researches focused on CO 2 fixation and utilization for production of algal biomass and high-value products, suggesting the possibility of capturing CO 2 and using the obtained algal biomass for various industrial applications. For example, Olofsson et al obtained high quality of microalgal biomass (lipids 20-30 % DW, proteins 20-28 % DW, carbohydrates 15-30 % DW) and high production when cultivated with flue gas addition (Olofsson et al 2015), and Kumar et al investigated the feasibility of using Chlorella sorokiniana for CO 2 sequestration from industrial flue gas with an inlet CO 2 content of 4.1 % (v/v) (Kumar et al 2014); both showed high feasibility of using cement industrial flue gas as a CO 2 source for microalgal cultivation.…”
Section: Informatics-based Analytical Methodsmentioning
confidence: 99%